The constitution of Shelley's poetry : the argument of language in Prometheus unbound - Duffy, Edward T. (Anthem nineteenth century studies., 2009)
'The Constitution of Shelley's Poetry' is a close philosophical reading of 'Prometheus Unbound' from the perspective of the argument or drama of language played out in its pages.